A Research about the 55th Verse of Surah an-Noor’s Implications for the Raj’at from the Sunni and Shi’ite Perspective - Reza Nowroozi; Mohsen Qasimpour (پژوهش‌های تفسیر تطبیقی, 2020)
Rij’at (Return) is one of the controversial arguments between the Islamic sects; the Shi’ites believe in the return to life of some believers and unbelievers (despite their physical death) after the appearance of Imam Mahdi (PBUH) and before the Day of Judgement while the Sunnis reject this belief. Those who believe in the Rij’at, in order to prove its feasibility, make a reference to the return of the dead to life among former communities through miracles such as raising the dead by Jesus Christ. They hold that the Rij’at will also occur in Akhir al-Zaman (End of the World) as there are various Qur’anic evidences such as the 55th verse of Surah an-Noor. In this holy verse, God has promised that the saints will ultimately overcome the world and make a government. The present study aims to review the exegetical ideas of Sunni and Shi’ite commentators in the interpretation of this verse and the results show that according to the evidences in the holy verse and the Ahadith, the Rij’at is inferred.